Hubungan Persepsi Pengembangan Karir Dengan Kinerja Karyawan Pdam Cabang Medan Kota - Afulina Sembiring; Azhar Azis (Universitas Medan Area, 2023)
The research objective was to determine the relationship between perceptions of career development and the performance of PDAM Medan City Branch employees. Employee performance is work performance or work results both in quality and quantity achieved by employees per unit time period as a level where employees meet/achieve work requirements specified in an organization in accordance with authority and responsibility. The type of research used is quantitative. The research population was 35 people and the sampling technique used was Total Sampling. The data analysis method uses the Product Moment Correlation technique from Pearson. The results of data analysis show that there is a significant positive relationship between perceptions of career development and employee performance where the value of rxy = 0.986, with p 0.000. The mean empirical mean value of perceptions of career development (90.74) is greater than the average hypothetical value (72.5) and the mean empirical mean value of employee performance (137.63) is greater than the average value hypotheses (105). The contribution of perceptions of career development to employee performance is 97.2% (R² = 0.972), while the rest (2.8%) is determined by other factors in this study that were not examined.